1986
DOI: 10.1177/014572178601200108
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Instructional Approaches Designed to Influence Food selection

Abstract: Eighty-nine children par ticipated in an education program designed to expose them to new foods and increase variety in their diet. Campers in an active involvement group prepared plain yogurt as part of their lesson in trying new foods; campers in a didactic instruction group had a traditional lecture/ discussion on trying new foods with a focus on yogurt; and a control group attended a general nutrition class. When campers were given a choice of a fruited yogurt pudding or peanut butter and crackers for a sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…[157][158][159][160][161][162][163][164][165][166] An additional five studies were identified but did not meet our quality criteria or did not report on relevant outcomes and were excluded from the review. [167][168][169][170][171] Study participants, identified as having type 1 diabetes, ranged in age from 8 to 15 years and were both male and female. Three studies were conducted among an all-white population, and one study reported a racially mixed population.…”
Section: Effectivenessmentioning
confidence: 99%
“…[157][158][159][160][161][162][163][164][165][166] An additional five studies were identified but did not meet our quality criteria or did not report on relevant outcomes and were excluded from the review. [167][168][169][170][171] Study participants, identified as having type 1 diabetes, ranged in age from 8 to 15 years and were both male and female. Three studies were conducted among an all-white population, and one study reported a racially mixed population.…”
Section: Effectivenessmentioning
confidence: 99%